Método de ressonância por impacto : obtenção de curvas mestras de módulo dinâmico e de ângulo de fase em misturas asfálticas brasileiras - Costa, Gessyca Menezes (2017)
The dynamic modulus is an important parameter in the mechanistic and empirical pavement design. It presents the stress-strain relationship for viscoelastic materials, such as asphalt mixtures. Obtaining the dynamic modulus is currently performed by mechanical testing and consisting of an axial sinusoidal load applying compression and measuring the resulting deformation. Thus, the assay requires a robust system, expensive and difficult to implement in field. To work around this limitation, this paper proposes an alternative methodology, more economical and easy to implement in paving, based in Mechanical Vibrations and which is widely used in the characterization of other materials, such as Portland cement concrete and ceramics. This methodology allows to obtain dynamic modulus and phase angle by determining the natural frequency of the material to apply a resilient thrust, called as resonance Impact test (RI). RI assay was performed under a wide range of temperatures, thus allowing the construction of the dynamic modulus master curve for Brazilian asphalt mixtures. It was not possible, in turn, to obtain a master curve for the dynamic modulo directly from the test result, for that, it was necessary an elaboration of sigmoidal and polynomial models. The models have a good correlation with the conventional mechanical test.